2011
DOI: 10.1590/s0074-02762011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rifampin-resistant genotypes in Mycobacterium tuberculosis by reverse hybridization assay

Abstract: We used a colorimetric reverse dot blot hybridization (CRDH) assay to detect the presence of mutations in a specific region of the rpoB gene, associated with rifampin (RIF) resistance, in a panel of 156 DNAs extracted from 103 RIF-sensitive and 53 RIF-resistant cultures of Mycobacterium tuberculosis. When compared with the antimicrobial susceptibility test (AST), the sensitivity and specificity of the CRDH were 92.3% and 98.1%, respectively. When compared with sequencing, the sensitivity and specificity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Our findings on the emergence of RIF/MXF-resistant mutants against the respective antibiotic from RIF persistence phase cells have substantiated and provided experimental proof that the antibiotic persistence phase cells are a reservoir from which mutants that are resistant to the same antibiotic or another antibiotic could emerge and get selected. Although the emergence of RIF/MXFresistant mutants from the RIF persistence phase cells in the present work was demonstrated using M. tuberculosis cells exposed to RIF in vitro, the identity of the mutations to those that were clinically relevant in TB patients the world over (52)(53)(54)(55)(56)(57)(58)(59)(76)(77)(78)(79)(80)(81)(82) indicated that the phenomenon of the emergence of RIF/MXF-resistant mutants from the RIF persistence phase might have been happening in vivo as well. Distinct from the previous studies, which showed emergence of genetically resistant Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa mutants upon short-duration exposure to sublethal concentrations of antibiotics (38)(39)(40)(41)(42), our study demonstrates that continuous prolonged exposure of M. tuberculosis cells to lethal concentrations of RIF causes de novo emergence of RIF-or MXF-resistant mutants from the RIF persistence phase cells at high frequency.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our findings on the emergence of RIF/MXF-resistant mutants against the respective antibiotic from RIF persistence phase cells have substantiated and provided experimental proof that the antibiotic persistence phase cells are a reservoir from which mutants that are resistant to the same antibiotic or another antibiotic could emerge and get selected. Although the emergence of RIF/MXFresistant mutants from the RIF persistence phase cells in the present work was demonstrated using M. tuberculosis cells exposed to RIF in vitro, the identity of the mutations to those that were clinically relevant in TB patients the world over (52)(53)(54)(55)(56)(57)(58)(59)(76)(77)(78)(79)(80)(81)(82) indicated that the phenomenon of the emergence of RIF/MXF-resistant mutants from the RIF persistence phase might have been happening in vivo as well. Distinct from the previous studies, which showed emergence of genetically resistant Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa mutants upon short-duration exposure to sublethal concentrations of antibiotics (38)(39)(40)(41)(42), our study demonstrates that continuous prolonged exposure of M. tuberculosis cells to lethal concentrations of RIF causes de novo emergence of RIF-or MXF-resistant mutants from the RIF persistence phase cells at high frequency.…”
Section: Discussionmentioning
confidence: 55%
“…The C¡T change at the 968th nucleotide position constituted 6.25% of the mutations (not shown in the schematic diagram, as it is outside the RRDR of the rpoB gene). These specific mutations have been reported in the rpoB gene of the RIF-resistant M. tuberculosis isolates from TB patients in different countries (52)(53)(54)(55)(56)(57)(58)(59). Thus, the RIF-resistant mutants isolated from the RIF persistence phase were genetically resistant mutants and not phenotypically resistant cells.…”
mentioning
confidence: 72%
“…After culture, DST was performed using the proportion method on Lowenstein-Jensen medium with the critical concentrations 0.2 g/ml INH, 40 g/ml RIF, 4 g/ml streptomycin (SM), and 2 g/ml ethambutol (EMB) (7), with a critical proportion of 1% indicating that an isolate is resistant. Samples were analyzed by DNA sequencing of the key regions involved in the development of resistance (rpoB, katG, and inhA) (8,9). After pretreatment using Petroff's method, the DNA extraction (directly from sputum), PCR amplification, strip hybridization, and interpretation of profiles of MTBDRplus were performed according to the manufacturer's instructions.…”
mentioning
confidence: 99%
“…The fact that most mutations known to confer resistance are localized to a specific region facilitates the development of molecular methods for their detection. Sequencing and hybridization-based assays have been commonly used and can define the precise mutations involved (4,7). Hybridization-based assays also provide a rapid and highthroughput approach (8).…”
mentioning
confidence: 99%